Brève description du système des relations du travail au Canada and The Current Trade Union Scene, Patterns and Trends - Dion, Gérard (Relations industrielles / Industrial Relations, 1976)
This article reviews "Brève description du système des relations du travail au Canada" by André Beaucage, and "The Current Trade Union Scene, Patterns and Trends" by W. Donald Wood.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z